Instalasi Proteksi Kebakaran pada Gedung Laboratorium Menggunakan Detektor Panas dan Detektor Asap - Gaspar Pereira Maia Pinto; Djoko Setyanto; Arka Dwinanda Soewono (G-Tech: Jurnal Teknologi Terapan, 2024)
The rise of various fire cases needs to be minimized through a fire protection system using equipment that is operated manually or automatically to detect and extinguish fires as early as possible. Changes in temperature and smoke appearing at the location can be parameters for early detection of the fire. This thesis successfully determines the number and point of detectors as well as fire protection installations in laboratory buildings in accordance with Indonesian National Standards (SNI) and Indonesian Regulations, namely the calculation of the number of detectors obtained was 44 units, divided into 22 heat detectors and 22 smoke detectors. On the 1st floor there are 16 detectors installed, 8 smoke detectors and 8 heat detectors, on the 2nd floor 16 units are installed consisting of 8 heat detectors and 8 smoke detectors, while on the 3rd floor there are 12 installed with 6 heat detectors and 6 smoke detectors.